الظواهر السبينية في تفكك –β النووي كتلة النترينو الإلكتروني السكونية وقانون انحفاظ –T (Latakia University Journal -Basic Sciences Series, 2018)
أدت دراسة تفكك بيتا النووي لاكتشاف شكل جديد من أشكال التأثيرات المتبادلة في الطبيعة(تاثيرات متبادلة ضعيفة),الذي قاد لاكتشاف جسيم جديد يدعى النترينو,الذي أسس لظهور فرع جديد في الفيزياء يدعى فيزياء النترينو,نظرا للدور الذي يلعبه في فيزياء الكون.كما تم تحديد بنية التيارات النووية الضعيفة.أما حتمية انحفاظ القوانين الفيزيائية فكانت دوما أداة لاستنباط قراءات جديدة بل ولادة نظريات جديدة لتوسيع فهمنا للكون.في هذا العمل تم دراسة لاتغير عبار  dwβ (احتمال التفكك) بالنسبة لدوران الزمن T, وذلك للارتباط التام لهذه الظاهرة مع بنية التيار النووي. كما تم تحديد قيمة كتلة النترينو الإلكتروني السكونية (        )  في بعض مجالات طيف الطاقة الالكتروني, وذلك اعتمادا على أحدث القيم التجريبية لمعامل الارتباطD. The study of Beta-decay led to establishing a new form of interaction in the nature (weak interactions), which resulted in discov     ering a new particle which has been named neutrino. The neutrino established a new branch of physics named neutrino physics, because of its importance in cosmic physics and in specifying the structure of weak nuclear currents. The certainty of conservation laws in physics has always been a tool to take new view, and to create modern theories to enhance our understanding of the universe. In this research, we have studied an invariant equation DWβ (decay probability) in relation to the time rotation, depending on the strong relation between this phenomenon with the structure of nuclear current. Also, based on the most recent experimental value for the correlation coefficient D, we have found the value of the rest electronic neutrino's mass (mve) in some intervals of the spectrum of electronic energy.